Exploring Learning Styles and Their Impact on Academic Achievement: A Study of Outstanding Students at Islamic University in Banda Aceh - Darmiah Darmiah; Syabuddin Gade; Saifullah Maysa; Silahuddin Silahuddin; Tria Marvida (STAI Hubbulwathan Duri, 2025)
Understanding individual learning styles is essential for enhancing educational outcomes, particularly among high-achieving students. This study explores the characteristics, distribution, and academic implications of learning styles—visual, auditory, and kinesthetic—among outstanding students at UIN Ar-Raniry, Banda Aceh. Employing a descriptive qualitative design, the research involved 24 students selected from nine faculties based on academic excellence. Data were gathered through semi-structured interviews, non-participant observations, and documentation, then analyzed using Miles and Huberman’s interactive model of qualitative analysis. The findings reveal that 37.5% of participants demonstrated a preference for visual learning, benefiting most from reading, writing, and visual representations. Auditory learners comprised 33.33%, favoring discussion-based and listening-centered activities, while 29.16% were kinesthetic learners who excelled through physical engagement and experiential learning. These results suggest that the dominant learning style among high-achieving students is visual, followed closely by auditory and kinesthetic preferences. The study indicates a potential correlation between learning style alignment and academic performance, although causality cannot be inferred due to methodological limitations. Nevertheless, the findings support the importance of differentiated instruction. Educators are encouraged to design flexible, multimodal learning environments that cater to diverse cognitive preferences. While the study offers insights specific to a localized educational context, broader generalizations require further empirical validation using larger and more diverse samples.